1993
DOI: 10.1093/bja/70.4.402
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Recoveries of Post-Tetanic Twitch and Train-of-Four Responses After Administration of Vecuronium With Different Inhalation Anaesthetics and Neuroleptanaesthesia

Abstract: We have studied recovery of post-tetanic twitch (PTT) and train-of-four (TOF) responses after administration of vecuronium in 100 patients under different inhalation anaesthetics and neuroleptanaesthesia. Patients were allocated randomly to five groups of 20 patients each to receive: neuroleptanaesthesia (droperidol and fentanyl), halothane, isoflurane, enflurane or sevoflurane (1 MAC in nitrous oxide and oxygen). The times from initial administration of vecuronium 0.2 mg kg-1 to the first appearances of T1, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 17 publications
2
28
2
Order By: Relevance
“…Recent studies on the effect of sevoflurane on duration of vecuronium -induced neuromuscular block yielded data that showed wide variation on the extent of prolongation [2][3][4]. However, there were several methodological differences compared with our study.…”
Section: Duration Of Actionmentioning
confidence: 62%
See 3 more Smart Citations
“…Recent studies on the effect of sevoflurane on duration of vecuronium -induced neuromuscular block yielded data that showed wide variation on the extent of prolongation [2][3][4]. However, there were several methodological differences compared with our study.…”
Section: Duration Of Actionmentioning
confidence: 62%
“…A lth o u g h sevoflurane appears to increase both in te n sity and duration of neuromuscular block in d u c e d by vecuronium and pancuronium [1][2][3][4], the m a g n itu d e of this effect has not been quantified in a hom ogeneous population. Such information is clini-procedures of an anticipated duration of ^ 90 min under general anaesthesia.…”
Section: P a Tie N Ts And M Eth O D Smentioning
confidence: 99%
See 2 more Smart Citations
“…11 Volatile anesthetics can also potentiate the neuromuscular block of non-depolarizing muscle relaxants in a concentration-dependent manner, by acting mainly at the post junctional membrane. 1 1 A recent report has shown that sevoflurane produces time-dependent potentiation of vecuronium neuromuscular block.…”
Section: Discussionmentioning
confidence: 99%